On the amino acids in the urine of dairy cows fed urea as the sole or partial source of nitrogen - Kreula, Matti; Ettala, Terttu (Agricultural and Food Science, 1977)
The urinary amino acids in free and bound form were determined quantitatively in dairy cows fed urea and ammonium nitrogen as the sole (0-cows) or partial (ULP-cows) source of nitrogen. For comparison, amino acid determinations were performed also on the urine of cows on ordinary silage-cereals feed and pasture feed (NorP-cows). The total amount (mg/1 urine) of the free amino acids was the smallest with 0-cows and the highest with NorP-cows on pasture feeding. The difference was mainly due to glycine ,which was found in significantly higher (P < 0.001) amounts with NorP-cows on pasture feeding. The proportion of glycine in the total identified free amino acids was 9.7 ± 9.0 % with 0-cows, 13.5 ± 5.1 % with ULP-cows, 7.7 ±3.4 % with NorP-cows on indoor feeding and 56.4 ±21.0 % with NorP-cows on pasture feeding. The corresponding figures for glutamic acid, which was quantitatively the most important amino acid with 0- and ULP-cows, were 36.5 ± 29.6 %, 19.8 ± 19.2 %, 5.7 ±4.0 % and 3.9 ± 2.1 % of the total free amino acids. Besides the identified amino acids, there were a number of unidentified amino acid derivatives in the free amino acid fraction in all the feeding groups. The total amount of amino acids freed by hydrolysis was the lowest with 0-cows. The proportion of glycine of the amino acids of the hydrolysate was48 % with 0-cows, 66 % with ULP-cows and 84 % with NorP-cows.